Assistance and socialization of fisherman safety signs in Muara Pantuan Village, Kabupaten Kutai Kartanegara - Arditiya Arditiya; Rizky Junanton; Dody Hasrizal Siahaan (Community Empowerment, 2021)
Fishing activity in the sea is one of the most dangerous jobs in the world. The incidence of fishing vessel accidents has continued to increase in the last 10 years. The threat of accidents due to bad weather, fog, collisions, loss of navigation, and others is a priority for ship crews sailing on the oceans. The importance of improving sailing skills to reduce the risks to zero accidents. Assistance and socialization of safety signs can improve the function of fishing skills of fishermen in Muara Pantuan Village, Anggana District, Kutai Kartanegara Regency.